The Effect Of Product Quality, Service And Price On Purchasing Decisions Of Cafe Ay Consumers In Kampung Pajak Labuhanbatu Utara - Cahnia, Murni; Pitriyani, Pitriyani (Amkop Management Accounting Review (AMAR), 2026)
At Cafe AY Kampung Pajak in North Labuhanbatu, we want to find out how much of an impact pricing, service quality, and product quality have on customers' final purchase choices. A quantitative technique based on survey methodology is used in this study. A total of 96 respondents were selected using a convenience sample approach and the Lemeshow formula; the population comprises all customers of Cafe AY. Questionnaires using a Likert scale from 1 to 5 were used to obtain the main data. Using SPSS version 25, the data analysis procedures include testing for validity and reliability as well as classical assumption testing, T-test, F-test, coefficient of determination analysis, and multiple linear regression analysis. A favorable and statistically significant influence of product quality on purchase choices is shown by the findings (t-value = 3.315, p = 0.001). The t-value for service quality is 2.535, and it is statistically significant at the 0.013 level. To top it all off, price is the most influential factor, having a positive and statistically significant impact (t=4.406, p=0.000). All of the factors had a substantial impact on consumers' choices to buy, with an F-value of 77.375 and a 0.000 level of significance. With a coefficient of determination of 0.716, these factors account for 71.6% of the variance in purchase choices.